دور المحاسبة العمومية في تنفيذ الرقابة على ميزانية البلدية دراسة حالة بلدية آفلو الأغواط - قيسي جهاد; قرادي عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
The subject of our study revolves around the role of public accounting in the implementation of control over the municipal budget, with a field study conducted in one of the municipalities, namely the municipality of Aflou, in the state of Laghouat. in implementing the municipal budget. This oversight is carried out through a group of various and integrated agencies in order to prevent all forms of manipulation of public money and protect it from corruption.